Did Yahweh Have a Consort? - Meshel, Zeʾev (The Biblical archaeology review, 1979)
The book of Kings describes a time during the 9th-7th centuries B.C. when the land was divided into two kingdoms—Judah in the south and Israel in the north. Phoenicia and Israel were linked by commerce and royal marriages and Hebrew monotheism struggled to resist the attraction of pagan gods. The prophets Elijah, Elisha, Amos […]